Correlation to predict heat transfer characteristics of a closed end oscillating heat pipe at critical state - Katpradit T. (2014)
This paper discusses experimental studies of the heat transfer characteristics at critical state of a closed end oscillating heat pipe (CEOHP). The parameters studied were the section lengths, working fluid and the dimensionless parameters of heat transfer characteristics at critical state. A set of 27 copper-tubed CEOHPs with internal diameters of 2.03, 1.06 and 0.66 mm; consisting of 5, 10 and 15 meandering turns and section lengths of 50, 100 and 150 mm was used in this study. Each CEOHP had a condenser, adiabatic and evaporator section of equal length. The working fluids used were R123, ethanol, and water with a filling ratio of 50% of total volume of the tube. The CEOHPs were set to operate at both vertical and horizontal orientations with a working temperature maintained at 60 ± 5 °C. The results show that the critical heat flux decreased as the section length increased, but increased with an increase in the latent heat of vaporization of the working fluid. The dominating dimensionless parameters on the heat transfer characteristics at horizontal heat mode were Ku, Di/Le, Ja and Bo while Ku, Di/L e, Ja, Bo and 1 + (ρv/ρl) 0.25 dominated at vertical heat mode. An additional dimensionless parameter that represents flooding phenomenon for vertical mode was 1 + (ρl/ρv)0.25. The correlations of critical heat flux and the parameters for prediction of the critical heat flux at the horizontal and the vertical heat mode were:Ku0=53680×DiLe1. 127×CpΔThfg1.417×Digρl-ρvσ0.5-1.32andKu90=0. 0002×DiLe0.92×CpΔThfg-0.212×Digρl-ρvσ0. 5-0.59×1+ρvρl0.2513.06with standard deviations (STD) of ±18% and ±29% respectively. © 2005 Elsevier Ltd. All rights reserved.